Korean Red ginseng supplements improve quality of life in patients with mild chronic pancreatitis symptoms: A prospective clinical trial - Joongyu Kang; Jin Ho Choi; Sang Hyub Lee; Junyeol Kim; Tae Seung Lee; Sung Hoon Chang; Yong Soo Song; In Rae Cho; Woo Hyun Paik; Ji Kon Ryu (Journal of Ginseng Research)
Background: Managing symptoms of chronic pancreatitis (CP) remains a significant challenge. Korean Red ginseng (KRG), a well-known herbal supplement, has shown potential benefits in various health conditions, prompting its investigation in CP patients. Methods: We conducted a single-arm, prospective clinical trial to evaluate the effect of KRG on quality of life in CP patients exhibiting mild symptoms, as defined by a Clinical Global Impression (CGI) score of 0 or 1. 40 patients were enrolled and assessed at baseline, as well as at 30, 90, and 180 days. The primary outcome was an improvement in CGI scores, with secondary outcomes including changes in Pancreatic Exocrine Insufficiency Questionnaire (PEI-Q) scores. Results: A total of 40 patients were enrolled in this study, and 39 participants were analyzed. Results showed significant improvements in CGI scores at all examined intervals (days 0–30, 0–90, 0–180; p < 0.05). The PEI-Q score also significantly improved from day 0 to day 180 (p < 0.05). Two adverse events (AEs) probably related to KRG were reported, and all AEs were improved with conservative managements. Conclusion: KRG supplementation significantly improves quality of life in CP patients with mild symptoms. These findings suggest that KRG may be a beneficial adjunct therapy in this patient population. Further research is needed to explore KRG’s pharmacological mechanisms, its use in combination with other treatments, and its effects in patients with more severe symptoms. (CRIS number: KCT0009681).